Avaliação da degradação de poliamida 11 empregada em cabos umbilicais por viscosidade inerente e reometria em regime oscilatório - Severino, Patrícia Baggio (2020)
Umbilical cable is one of the main systems for monitoring, powering, and supplying chemicals foroffshore oil and gas wells. Polyamide 11 (PA 11) composes the ducts for the chemical injection andcan suffer withseveral degradation processes. Little is known about the degradation resulting from the chemical contact between the applied products and the PA 11. Currently, the inherent viscosity is the analytical technique most used by the oil industry in monitoring the polyamide 11degradation, as it allows inferring about the polymeric molar mass. However, this technique makes use of toxic solvents, and generates hazardous waste. A more compliant alternative with the concepts of green chemistry and operational safety, is the use of rheological analyzes in a small amplitude oscillatory regime. This technique allows to evaluate changes in the molecular structure of the polymer, provides information on the molar mass distribution, storage module (G') and loss module (G''), does not use solvents and is an automatedand robust technique. In this sense, the objective of this work was to establish a correlation between the analysis of oscillatory rheometry with the inherent viscosity tomonitor the degradation of polyamide 11. It were analyzed polyamides with four different levels of degradation and two chemical products, A ( naphtha base, diesel oil, butoxyethanol and mercaptoethanol) and B (condensed aldolic base and ethanol), most used during oil and gas production as corrosion inhibitors and H2S scavengers, respectively. It was observed through the values of corrected inherent viscosity (VIC) and viscosimetric molar mass (̅̅̅̅) that extrusion reprocessing resulted in PA 11 with different molar masses possibly due to hydrolytic degradation, associated with polycondensation reactions. By analyzing the Cole-Cole curve, an increase in the molar mass distribution was observed. It was also possible to verify that the immersion time and the type of degrading chemical medium has a greater impact on the degradation of PA11. Since the Newtonian plateau was not identified in the viscosity curve as a function of frequency, an alternative to the Cox-rule Merz was the use of β, which showed a greater variation between the values obtained by VIC and by rheometry for the mostdegraded samples. A good correlation was found between rheometry and viscosity in solution, indicating that the methodology used can be used to measure the variation in the molar mass of the polyamide 11.